Charged particle single nanometre manufacturing - Prewett, Philip D.; Hagen, Cornelis W.; Lenk, Claudia; Lenk, Steve; Kaestner, Marcus; Ivanov, Tzvetan; Ahmad, Ahmad; Rangelow, Ivo W.; Shi, Xiaoqing; Boden, Stuart A.; Robinson, Alex P. G.; Yang, Dongxu; et al. (Beilstein Journal of Nanotechnology, 2018)
Following a brief historical summary of the way in which electron beam lithography developed out of the scanning electron microscope, three state-of-the-art charged-particle beam nanopatterning technologies are considered. All three have been the subject of a recently completed European Union Project entitled “Single Nanometre Manufacturing: Beyond CMOS”. Scanning helium ion beam lithography has the advantages of virtually zero proximity effect, nanoscale patterning capability and high sensitivity in combination with a novel fullerene resist based on the sub-nanometre C60 molecule. The shot noise-limited minimum linewidth achieved to date is 6 nm. The second technology, focused electron induced processing (FEBIP), uses a nozzle-dispensed precursor gas either to etch or to deposit patterns on the nanometre scale without the need for resist. The process has potential for high throughput enhancement using multiple electron beams and a system employing up to 196 beams is under development based on a commercial SEM platform. Among its potential applications is the manufacture of templates for nanoimprint lithography, NIL. This is also a target application for the third and final charged particle technology, viz. field emission electron scanning probe lithography, FE-eSPL. This has been developed out of scanning tunneling microscopy using lower-energy electrons (tens of electronvolts rather than the tens of kiloelectronvolts of the other techniques). It has the considerable advantage of being employed without the need for a vacuum system, in ambient air and is capable of sub-10 nm patterning using either developable resists or a self-developing mode applicable for many polymeric resists, which is preferred. Like FEBIP it is potentially capable of massive parallelization for applications requiring high throughput.
Keywords: charged particle beams; electron; field emission; ion; nanolithography